2019
DOI: 10.1016/j.ibror.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

An in silico investigation on the inhibitory potential of the constituents of Pomegranate juice on antioxidant defense mechanism: Relevance to neurodegenerative diseases

Abstract: Elevation in the levels of reactive oxygen and nitrogen species (RONS), and downregulation of cellular antixoidants, have ubiquitously been reported from studies in animal models of neurodegenerative diseases, including Parkinson’s disease (PD) and Alzheimer’s disease (AD). Thus, plant-derived compounds are widely being investigated for their beneficial effects in these models. However, while studies have reported antioxidant potentials of several phytochemicals, a large number of studies have demonstrated dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 64 publications
1
24
1
Order By: Relevance
“…Computational studies performed with different pomegranate juice constituents revealed that they can act as pro-oxidants or antioxidants. Molecular docking studies seem to be controversial, as they have determined that urolithin A may inhibit cytosolic enzymes such as catalase, superoxide dismutase, and glutathione [34]; however, urolithin A seems to improve the activity of these enzymes in our present study. With the aim of elucidating molecular mechanisms involved in the cytoprotective and antioxidant properties of urolithin A, peroxiredoxins expression (Prx) was quantified in this work.…”
Section: Discussioncontrasting
confidence: 67%
“…Computational studies performed with different pomegranate juice constituents revealed that they can act as pro-oxidants or antioxidants. Molecular docking studies seem to be controversial, as they have determined that urolithin A may inhibit cytosolic enzymes such as catalase, superoxide dismutase, and glutathione [34]; however, urolithin A seems to improve the activity of these enzymes in our present study. With the aim of elucidating molecular mechanisms involved in the cytoprotective and antioxidant properties of urolithin A, peroxiredoxins expression (Prx) was quantified in this work.…”
Section: Discussioncontrasting
confidence: 67%
“…Results showed that among others, urolithin A, urolithin A glucuronide, and urolithin B have the potential to inhibit catalase, SOD (superoxide dismutase), GR (glutathione reductase), GPx (glutathione peroxidase), and GST (glutathione-S-transferase), by interfering with their active catalytic sites. These findings suggest that these compounds can act both as prooxidants and as antioxidants [42].…”
Section: Urolithin Activity In the Modulation Of Oxidative Stressmentioning
confidence: 90%
“…Pelargonidin alleviates 6-OHDA-induced neurotoxicity through the suppression of lipid oxidation in a rodent model of PD. Blueberry extracts, such as pelargonidin, peonidin, and petunidin, have multiple health-promoting properties, and it has been largely revealed that blueberries and pomegranate extract can protect neurons against neurotoxic events, such as apoptosis, inflammation, and OS ( Table 3 ) [ 187 , 188 , 189 ].…”
Section: Natural Antioxidants: Flavonoidsmentioning
confidence: 99%